A comparison of three models on air infiltration for residential building energy simulation. Issue 3 (1st October 2016) - Ren, Zhengen; Chen, Dong
ABSTRACT: To evaluate potential air infiltration model improvement for residential building energy simulation, three infiltration models have been developed and implemented into AccuRate, a housing energy star rating tool widely used in Australia. This paper presents a comparison of the calculated air infiltration rates and building energy performance using the three models. Case studies are made for eight houses with various envelope leakages under different weathers Australia (Melbourne – heating dominated, Sydney – balanced heating and cooling, and Cairns – cooling dominated). The results show that there are up to 37% differences in the calculated average infiltration rates between these three models for both Melbourne and Sydney, and 40% in Cairns. Up to 13% and 6.7% differences were observed in the modelled annual energy needs for space heating/cooling in Melbourne and Sydney, respectively, among the three models, and up to 20% differences in the simulated energy needs for cooling in Cairns. The simple approaches ignored impact factors such as system operation, envelope leakage and stack effect variation due to indoor–outdoor temperature differences. The multizone model accounted all these factors and should be used for predicting infiltration in the future. However, the executing speed using multizone model will need to be improved.